Consumption of nuts and seeds and pancreatic ductal adenocarcinoma risk in the European Prospective Investigation into Cancer and Nutrition. Issue 1 (6th June 2019) - Obón‐Santacana, Mireia; Luján‐Barroso, Leila; Freisling, Heinz; Naudin, Sabine; Boutron‐Ruault, Marie‐Christine; Mancini, Francesca Romana; Rebours, Vinciane; Kühn, Tilman; Katzke, Verena; Boeing, Heiner; Tjønneland, Anne; Olsen, Anja; et al.
Abstract : Four epidemiologic studies have assessed the association between nut intake and pancreatic cancer risk with contradictory results. The present study aims to investigate the relation between nut intake (including seeds) and pancreatic ductal adenocarcinoma (PDAC) risk in the European Prospective Investigation into Cancer and Nutrition (EPIC) study. Cox proportional hazards models were used to estimate hazards ratio (HR) and 95% confidence intervals (95% CI) for nut intake and PDAC risk. Information on intake of nuts was obtained from the EPIC country‐specific dietary questionnaires. After a mean follow‐up of 14 years, 476, 160 participants were eligible for the present study and included 1, 283 PDAC cases. No association was observed between consumption of nuts and PDAC risk (highest intake vs nonconsumers: HR, 0.89; 95% CI, 0.72–1.10; p ‐trend = 0.70). Furthermore, no evidence for effect‐measure modification was observed when different subgroups were analyzed. Overall, in EPIC, the highest intake of nuts was not statistically significantly associated with PDAC risk. Abstract : What's new? Environmental and lifestyle factors probably play a major role in the development—or prevention—of pancreatic cancer (PC). For example, might the inclusion of nuts in one's diet reduce the risk of PC? Results of previous studies have been contradictory. In this analysis of data from the large, prospective EPIC study, the authors found no significant protective role for nuts or seeds against PC.